2013
DOI: 10.1063/1.4819136
|View full text |Cite
|
Sign up to set email alerts
|

Improved coarse-grained model for molecular-dynamics simulations of water nucleation

Abstract: We developed a new coarse-grained (CG) model for water to study nucleation of droplets from the vapor phase. The resulting potential has a more flexible functional form and a longer range cutoff compared to other CG potentials available for water. This allowed us to extend the range of applicability of coarse-grained techniques to nucleation phenomena. By improving the description of the interactions between water molecules in the gas phase, we obtained CG model that gives similar results than the all-atom (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
2
17
1
Order By: Relevance
“…In Fig. 6c values of J N are reported as a function of the supersaturation S, clearly showing a significant extension of the accessible nucleation rates domain, which is increased up to ten orders of magnitude compared to the domain typically accessible by standard molecular dynamics 12,23,24,33,34 . The surface tension γ obtained from the fitting of the J N values computed from WTmetaD corresponds to γ = 16.9 mN/m, a value that nicely extrapolates the data of Goujon et al 35 for the same system in the temperature range between 85 K and 135 K as shown in the Supplementary Information (SI).…”
Section: Nucleation Ratesmentioning
confidence: 86%
“…In Fig. 6c values of J N are reported as a function of the supersaturation S, clearly showing a significant extension of the accessible nucleation rates domain, which is increased up to ten orders of magnitude compared to the domain typically accessible by standard molecular dynamics 12,23,24,33,34 . The surface tension γ obtained from the fitting of the J N values computed from WTmetaD corresponds to γ = 16.9 mN/m, a value that nicely extrapolates the data of Goujon et al 35 for the same system in the temperature range between 85 K and 135 K as shown in the Supplementary Information (SI).…”
Section: Nucleation Ratesmentioning
confidence: 86%
“…47 We also put the experimental data for water nucleation. 6,20,22,23,26,27 For the experimental results and Zipoli et al, 57 T c is set to be 647 K. 20 From Fig. 5, J seems to be scaled by ln S/(T c /T − 1) 1.5 , but is not proportional to it.…”
Section: B Nucleation Ratementioning
confidence: 99%
“…The nucleation rates by SP model (solid 47 and Zipoli et al, 57 respectively. In Zipoli et al, 57 we use the nucleation rates at 350 K. The nucleation rates by SP model (solid curve) are also plotted.…”
Section: A a Typical Casementioning
confidence: 99%
See 1 more Smart Citation
“…MD nucleation simulations of mW water have been carried out, yet only on small systems with relatively high nucleation rates [44,45]. The monoatomic water model proposed by Zipoli et al (2013) [46] offers similar advantages. However, we found that short-range potentials require extremely long equilibration times to form the correct equilibrium abundance of small clusters (dimers, trimers, etc.)…”
Section: Introductionmentioning
confidence: 99%